Розрахунок геометричних параметрів обмежених струменів рідини - Орел, Вадим Ігорович (My University, 2004)
In paper the computation of geometrical parameters of the restricted jets of a liquid at sudden expansions of pipes are presented.
Keywords: 532.522.2:532.542:532.556.2